PENGARUH PENERAPAN ANGGARAN BERBASIS KINERJA TERHADAP AKUNTABILITAS PUBLIK PADA INSTANSI PEMERINTAH (Studi Pada Badan Pengelola Keuangan Dan Aset Daerah Kota Kendari) - Safaruddin, Safaruddin; Basri, Sutriana (JURNAL AKUNTANSI DAN KEUANGAN, 2016)
ABSTRACThis research aimed to examine the effect of the application of performance-based budgeting to public accountability in government agencies. Primary data in this research were obtained from the perceptions of employees in Badan Pengelola Keuangan Dan Aset Daerah (BPKAD) Kota Kendari. Perceptions of respondents was measured by responses to questionnaires that uses ordinal measurement with 5-point Likert scale. The statistical method used to test the hypothesis is simple linear regression analysis by means of SPSS version 20.The results of this research indicate that the application of performance-based budgeting significant effect on public accountability in government agencies. This research shows the results of determination coefficient application  performance-based budgeting to the public accountability of R2 = 0.343. The figure has meaning that the application of performance-based budgeting contribution towards public accountability was 34.3%, while the remaining 65.7% was obtained from the contribution of other factors. Keywords: Performance-Based Budgeting and Public Accountability.